Risiko Harga Ayam Broiler Pola Kemitraan dan Mandiri di Kabupaten Bekasi - Gita Vinanda; Harianto Harianto; Lukytawati Anggraeni (Journal of Food System & Agribusiness, 2018)
Constraints often faced by broiler breeders in West Java Province are the selling price of broiler chickens that are not always stable. One of the selling prices of broiler chickens is created by the conditions of demand and supply in the market, so that in certain conditions when the number of broilers increases, the selling price of chicken can be very low and when the number of broilers decreases due to constraints in the production process, the selling price of chicken can increase . The purpose of this study was to measure the level of price risk faced by broiler chickens in Bekasi Regency. This research was conducted in Bekasi Regency, West Java Province. Sampling is done by purposive and snowballing method. The number of samples is divided into 35 independent breeders and 39 partner farmers. Data collection is done through interviews directly with the respondent farmers using a questionnaire. The collected data is then analyzed using the coefficient of variation. The results of the study show that the price risk faced by independent farmers is much smaller than the price risk received by partner farmers. Keywords: broiler chicken, partnership, price risk.